Alveolitis seca: una revisión de la literatura - Vergara Buenaventura, Andrea (2014)
ABSTRACT Dry socket is the most common postoperative complication, due to problems in alveolar wound healing after tooth extraction. The management of this condition aims to control pain during the healing period, and is mainly achieved with palliative drugs. The aim of this literature review is to obtain sufficient information on the causes and any other factors that could be involved in this post-operative complication, as well as the currently available treatment options.